2004
DOI: 10.1016/s0014-5793(04)00374-6
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and their endogenous inhibitors in neuronal physiology of the adult brain

Abstract: More than 20 matrix metalloproteinases (MMPs) and four of their endogenous tissue inhibitors (TIMPs) act together to control tightly temporally restricted, focal proteolysis of extracellular matrix. In the neurons of the adult brain several components of the TIMP/MMP system are expressed and are responsive to changes in neuronal activity. Furthermore, functional studies, especially involving blocking of MMP activities, along with the identification of MMP substrates in the brain strongly suggest that this enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 30 publications
3
67
0
2
Order By: Relevance
“…Studies also showed that invading inflammatory cells can provide the major source of the MMP activity (Kaczmarek et al, 2002). Moreover, MMP-9 is expressed in adult brain neurons and is responsive to changes in neuronal activity (Dzwonek et al, 2004). Combined with the results of previous research (Castro-Sanchez et al, 2011), we hypothesized that MMP-9 overexpression and activation after cerebral ischemic injury may be regulated by its upstream molecule (DDR1) via inflammatory responses, which provided a reliable basis for our next experiments.…”
Section: Discussionmentioning
confidence: 73%
“…Studies also showed that invading inflammatory cells can provide the major source of the MMP activity (Kaczmarek et al, 2002). Moreover, MMP-9 is expressed in adult brain neurons and is responsive to changes in neuronal activity (Dzwonek et al, 2004). Combined with the results of previous research (Castro-Sanchez et al, 2011), we hypothesized that MMP-9 overexpression and activation after cerebral ischemic injury may be regulated by its upstream molecule (DDR1) via inflammatory responses, which provided a reliable basis for our next experiments.…”
Section: Discussionmentioning
confidence: 73%
“…In fact, after KA treatment, we found a decrease of gelatinolytic (ϭMMP) activity in the ML and GCL by in situ zymography, indicating that KA indeed causes a reduction of MMP activity in the regions where surviving Cajal-Retzius cells are located. It is possible that tissue inhibitors of metalloproteases (TIMPs), known to control the activity of MMPs (42), are involved in the down-regulation of MMP activity in our system. In fact, TIMP-1 expression has been shown to increase rapidly in the hippocampus following seizures (43)(44).…”
Section: How Does Epileptic Activity Affect Reelin Processing?mentioning
confidence: 99%
“…Four mammalian TIMPs have been cloned and characterized by primary structure and functional analyses (Dzwonek et al, 2004;Lambert et al, 2004). TIMP-1 is secreted as a 28-kDa glycoprotein that binds tightly to the active form of multiple MMPs.…”
Section: Introductionmentioning
confidence: 99%